Evaluating poor working conditions and health problems faced by carpet weavers in Kashmir: a qualitative analysis - Tanveer Ahmad Khan; Shaista Qayum (International Journal of Qualitative Studies on Health & Well-Being, 2024)
This study provides a comprehensive exploration of the working conditions and associated health challenges faced by carpet weavers in Kashmir. The detailed examination of various factors contributes significantly to understanding the intricacies of their daily lives and provides valuable insights into an often-overlooked aspect of occupational health. The data was collected through 22 individual interviews and 5 Focus Group Discussions (FGDs). A semi-structured interview schedule was used to collect data allowing researchers to engage with participants. The results of the study emphasize that carpet weavers are not satisfied with the existing working conditions of the workshops they work in. Most carpet weavers suffer from multiple and sometimes chronic health ailments like musculoskeletal problems, respiratory problems, skin problem, fatigue and other health problems such as abdominal pain, nose problem, and anaemia owing to the unsafe working environment, long working hours, inappropriate sitting postures, poorly designed tools, exploitative circumstances, and low wages. The study recommends need for recognition of carpet weavers as vulnerable workers. The call for improved working conditions, better infrastructure, and awareness initiatives aligns with the goal of fostering a healthier and supportive environment for these workers. There is a significant need to address the identified health problems to safeguard both the carpet industry and the livelihoods of the weavers.